ChemInform Abstract: Bulk Silicon Crystals with the High Boron Content, Si1—x Bx: Two Semiconductors Form an Unusual Metal. Issue 46 (18th November 2014) - Ovsyannikov, Sergey V.; Gou, Huiyang; Karkin, Alexander E.; Shchennikov, Vladimir V.; Wirth, Richard; Dmitriev, Vladimir; Nakajima, Yoichi; Dubrovinskaia, Natalia; Dubrovinsky, Leonid S.
Abstract Bulk diamond‐structured Si1‐xBx alloys (x ≤ 2.4 at.%) are prepared by high‐temperature/high‐pressure synthesis using Si and β‐Boron crystals (hexagonal BN capsules in multi‐anvil press, 1573—1973 K, 3—20 GPa, 1—2 h).